Comparison of efficacy and safety of entecavir and switching from entecavir to tenofovir alafenamide fumarate in chronic hepatitis B: Long‐term effects from a prospective study. Issue 7 (7th May 2021) - Hagiwara, Satoru; Nishida, Naoshi; Ueshima, Kazuomi; Yoshida, Akihiro; Minami, Yasunori; Kudo, Masatoshi
Abstract: Aim: Both entecavir (ETV) and tenofovir alafenamide fumarate (TAF) are widely used to treat chronic hepatitis B (CHB) in Japan. However, it remains unclear whether the efficacy of TAF in decreasing the hepatitis B surface antigen (HBsAg) level, and its safety, are superior to those of ETV. This study aimed to report the long‐term effects and safety of 96‐week ETV and TAF treatment in patients with CHB. Methods: A prospective comparative observational study was undertaken on the following two groups: patients with CHB who received continuous ETV ( n = 32) and patients with CHB who were switched from ETV to TAF upon request ( n = 48). The HBsAg, urinary β 2‐microglobulin ( β 2MG)/creatinine (Cr), urinary N‐acetyl‐ β ‐D‐glucosaminidase (NAG)/Cr, and serum alanine aminotransferase (ALT) levels, estimated glomerular filtration rate (eGFR), and bone mineral density (lumbar spine and femur) at 96 weeks were compared. Results: The two groups did not significantly differ with respect to mean age, male / female patient ratio, or rate of hepatitis B e antigen‐positive status. The mean changes in serum HBsAg level and eGFR at 96 weeks were not significantly different between the two groups. The β 2MG/Cr and NAG/Cr levels at 96 weeks were similar between the two groups. Additionally, the bone mineral density of the lumbar spine and femur as well as the serum ALT did not significantly differ. Conclusions: When compared with patients who received continuous ETV, those who were introduced to TAF after ETV showed similar effects in terms of the decrease in HBsAg level and safety.